East Asia in the aftermath: Was there a crunch? - Swati R. Ghosh; Atish R. Ghosh (Deutsche Bank Research, 2000)
This paper investigates whether there was a credit crunch in East Asia during the recent financial and economic crises. Motivated by widespread concern that, over and above any increases in real interest rates, corporates may have also faced credit rationing, we adopt an explicit disequilibrium framework for analyzing the behavior of real credit with a view to assessing whether the supply of, or demand for credit has been a binding constraint. The findings highlight the dynamics associated with a credit crunch. We find evidence of a »credit crunch« in all three crisis countries (Indonesia, Korea, Thailand) in the period immediately following the crisis as the banking system distress deepened, and the supply of (real) credit declined. Thereafter, however, credit demand also fell sharply as economic recession took hold and corporate bankruptcies increased. By the end of the first quarter of 1998, therefore, the constraining factor was the demand for credit. We conclude that, beyond the initial crisis period, there is little evidence of a credit crunch at the aggregate level, although high real interest rates - and credit rationing of individual firms - may have continued to contribute to the difficulties of the corporate sector.
Keywords: 330; emerging markets; credit crisis; Bankenkrise; Kreditmarkt; Zins; Indonesien; Südkorea; Thailand